Distributed Newspaper Delivery System - Ali Shehadeh, Nael Hassan (2002)
This project alms to use distributed client/server environment instead of the traditional manual registration newspaper delivery system. This system will be developed using Microsoft Visual Basic Version 6.0 (VB6.0) and the database by SQL server (2000) as the development platform. The output of the project will be two executable files (the client and the server), which will use Windows 2000 operating system as a delivery platform. The specific advantage of this system is that it has specific calculation such as billing which saves time for the users. The proposed project will try to make the graphical user interface (GUI) as easy and understandable possible to the users (User Friendly).